How does climate exacerbate root causes of conflict in Mali? An econometric analysis - Kangogo, Daniel; Läderach, Peter R.D.; Grazia Pacillo (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Mali, using a two-stage econometric approach. The findings show that food insecurity is the mechanism through which climate change influences conflict. Climate change indirectly exacerbates conflict by adversely affecting agricultural production and food security.